Tracing highly siderophile elements through subduction: Insights from high-pressure serpentinites and 'hybrid' rocks from alpine corsica - Crossley, R.J.; Evans, Katy; Evans, Noreen; Bragagni, A.; McDonald, B.J.; Reddy, Steven; Speelmanns, I.M. (OXFORD UNIV PRESS, 2020)
The highly siderophile elements (HSE) include the economically critical platinum group elements (PGE; Os, Ir, Ru, Rh, Pt, Pd, Au and Re), gold and rhenium. The HSE are redox sensitive in mantle and seafloor environments and have a strong affinity to iron and sulphur, therefore their distribution within the subducted mantle lithosphere record changes to oxidation state and sulphidation. The mobility of the HSE during subduction has important implications for Re-Os isotopic signatures in the mantle, and the formation of Cu-Au arc-related ore deposits. In this study, subducted rock samples from Alpine Corsica are used to track the HSE in serpentinites and hybrid ultramafic-mafic rocks through the subduction cycle. A comparison of bulk-rock HSE concentrations with those in pre-subduction analogues provides insights into the transfer of the HSE throughout the subduction cycle. Serpentinites subducted to blueschist-eclogite-facies conditions have similar HSE concentrations to primitive upper mantle (PUM) concentrations, therefore it is concluded that the HSE are not mobilized from serpentinites on the scale of the whole-rock or greater. Therefore, as suggested in previous studies, crustal lithologies may be more important contributors of the HSE to the sub-arc mantle, particularly Pt, Pd and Re. In contrast, HSE concentrations in hybrid rocks (talc schist and chlorite schist) deviate from protolith concentrations. Rhenium is higher in the talc schist, and Ir and Ru are lower in the chlorite schist than in the PUM, or possible mafic protoliths. Mineral parageneses place temporal constraints on the growth of hosts to the HSE (sulphides, oxides and metal alloys), and record changes to the activities of oxygen and sulphur (aO2-aS2), and hence redox conditions, from pre-subduction to exhumation. Laser ablation inductively coupled plasma mass spectrometry was used to determine the HSE concentrations in sulphides and oxides, and the detection of small (2-25 mm2) platinum group minerals utilized high-resolution SEM mapping techniques. The prograde and retrograde sulphides have lower HSE concentrations compared with sulphides from pre-subduction settings. Therefore, the redistribution of the HSE on a mineral scale from sulphides to alloys and/or other sulphides has occurred within the serpentinites, which may reflect more reducing conditions during serpentinization or subduction, consistent with the results of thermodynamic modelling. In contrast, the mineral assemblages in the hybrid rocks imply an increase in the extent of sulphidation and oxidation, and higher fluid:rock ratios during exhumation, coincident with Re enrichment in the talc schist, and a decrease in the concentrations of Ir and Ru in the chlorite schist, at length scales greater than those of the rock samples. Therefore, hybridization of lithologies at the slab-mantle interface may enhance the transfer of the HSE to the sub-arc mantle. If Re transfer from the slab to the sub-arc mantle is possible, this questions the robustness of Re-Os isotope signatures as tracers of crustal recycling.